2017
DOI: 10.3233/jad-170275
|View full text |Cite
|
Sign up to set email alerts
|

Ubisol-Q10 (a Nanomicellar Water-Soluble Formulation of CoQ10) Treatment Inhibits Alzheimer-Type Behavioral and Pathological Symptoms in a Double Transgenic Mouse (TgAPEswe, PSEN1dE9) Model of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…In addition, CoQ10 oral administration restores oxygen consumption levels in the brain of aged animals [74] and exerts antihyperglycemic effects [23-25]. In addition, previous reports have indicated the usefulness of CoQ10 supplementation on memory processing by improving hippocampal cholinergic function via increasing cholineacetyltransferase and decreasing acetylcholinesterase activities [53], neurogenesis via reducing amyloid-β formation [75, 76], reducing oxidative stress markers, and increasing ATP levels in hippocampus and cortex [53]. Therefore, the sum of CoQ10 supplementation on decline of hyperglycemia, oxidative stress, neuronal apoptosis, and improved cholinergic activity, vascular function, brain blood flow, and metabolism may contribute to the attenuation of DM-induced memory impairment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CoQ10 oral administration restores oxygen consumption levels in the brain of aged animals [74] and exerts antihyperglycemic effects [23-25]. In addition, previous reports have indicated the usefulness of CoQ10 supplementation on memory processing by improving hippocampal cholinergic function via increasing cholineacetyltransferase and decreasing acetylcholinesterase activities [53], neurogenesis via reducing amyloid-β formation [75, 76], reducing oxidative stress markers, and increasing ATP levels in hippocampus and cortex [53]. Therefore, the sum of CoQ10 supplementation on decline of hyperglycemia, oxidative stress, neuronal apoptosis, and improved cholinergic activity, vascular function, brain blood flow, and metabolism may contribute to the attenuation of DM-induced memory impairment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, open field mice primarily attended to which corner previously had no object but not to any object's specific non-spatial features while they thigmotaxically ran around the periphery of the chamber. Our most recent study with a transgenic mouse model of AD [81], animals were only exposed to an enclosed Y-maze in a 2-object variation of the NL/NOR task. Only unprotected transgenic mice failed to explore the familiar but moved object any more than the other two unmoved objects (trial 2) but showed heightened exploration of the novel object (trial 3) as well as the wild type and protected transgenic mice.…”
Section: Transgenic Animal Models Of Admentioning
confidence: 99%
“…Ubisol-Q 10 also prevented oxidative SIPS and enhanced activation of autophagy via upregulation of beclin-1 (a major regulator of autophagy) in PS-1 mutated fibroblasts [8]. Additionally, Ubisol-Q 10 at low doses (orally delivered) reduced circulating Aβ peptide, reduced oxidative stress, had positive effects on long-term and working memory, and drastically inhibited β-amyloid plaque formation in 16month-old transgenic AD mouse brains [7].…”
Section: Introductionmentioning
confidence: 99%
“…The exact etiology of AD is unknown, but some pathological features include the formation of toxic β-amyloid plaques and neuro-fibrillary tangles and neuron loss in the hippocampus [5,6]. Furthermore, there are a number of mechanisms associated with AD which include the following: (1) increased oxidative stress [7], (2) mitochondrial dysfunction, and (3) impaired autophagy activity and accumulation of defective proteins/organelles [8]. Furthermore, it is hypothesized that these brain lesions/biochemical mechanisms occur before the symptoms of AD show implying that neuronal death is happening before disease diagnosis [9].…”
Section: Introductionmentioning
confidence: 99%